Decision Support System for Determining the Location of Bank Indonesia Gorontalo Offices Using the Weighted Product Method - Siddiq Fahriady Seban (Journal of Intelligent Decision Support System (IDSS), 2021)
The decision support system for determining the location of the Bank Indonesia Gorontalo office is an application program created to be used by the Bank Indonesia Gorontalo office in determining the best alternative land that will become the land for the Bank Indonesia Gorontalo Office, the assessment of this alternative land is modeled based on alternative data compiled with the following criteria. has been determined. The data and alternative criteria were processed using the Fuzzy Multiple Attribute Decision Making (FMADM) Weigted Product (WP) method. In using this method, it is hoped that the system application that will be used can assist the decision-making process so as to obtain the best alternative land which will later be used as land for the Bank Indonesia Gorontalo office